A experiência estética por meio da literatura infantil - Maia, Jessica Louise Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The children's literature is fundamental in the formation of the individual, they bring with them the various modalities of artistic visual processes which is another look at the text in the children's book and has no commitment to represent reality with fidelity, but to create and invent. In this context, this work proposes lessons that will bring the artistic aesthetic experience in the classroom, from the visual languages of children's books, and new experiences can arise, provoking feelings and feelings. Seizing the relationship of children's literature and aesthetic experience for teaching art in Elementary School, this project will add my experience as a professional, being relevant for bringing new projects and forms of art teaching in schools, leading students to a path that develops imagination and learning.

A literatura infantil é fundamental na formação do indivíduo, trazem com eles as diversas modalidades de processos visuais artísticos que é um outro olhar sobre o texto no livro infantil e não possui compromisso em representar com fidelidade a realidade, mas de criar e inventar. Nesse contexto, esse trabalho propõe aulas que trarão a experiência estética artística em sala de aula, a partir das linguagens visuais artísticas dos livros infantis, podendo surgir novas experiências, provocando sensações e sentimentos. Apreendendo a relação da literatura infantil e experiência estética para ensino da arte no Ensino Fundamental, esse projeto acrescentará minha experiência como profissional, sendo relevante por trazer novos projetos e formas de ensino da arte nas escolas, levando os alunos a um caminho que passa a desenvolver a imaginação e o aprendizado.
Keywords: Artes; Arte e educação; Literatura infantojuvenil